Malowidło „Św. Jan Chrzciciel w pejzażu” z Muzeum w Krośniewicach - Kowalczyk, Justyna (Sztuka i Kultura, 2015)
The paper is an attempt at identification of the painting’s author. A formal analysis of this high quality artwork revealed its Northern European origin not devoid of Italian influences, especially in its figural part. Detailed comparisons provided for conclusion that two separate artists were engaged its creation: Jan Wildens (landscape background) and Cornelis Schut (human figure), both disciples of Peter Paul Rubens, whose style is indirectly legible in the composition. The canvas thus seems to document yet another case of well-proven cooperation of these two specialized Flemish painters.